PELATIHAN KEPEMIMPINAN DIGITAL UNTUK MEMPERKUAT TATA KELOLA ORGANISASI KEMAHASISWAAN DI STAI PUTRA GALUH CIAMIS - Nono Mulyono; Ani Herniawati; Yusuf Hidayat (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) – Sekolah Tinggi Agama Islam (STAI) Pelita Nusa Bandung Barat, 2026)
The use of digital technology in student organisations has not always been followed by adequate leadership and organisational governance skills. This community service activity aims to increase students' understanding and readiness in implementing digital leadership to support the management of student organisations that are planned, collaborative, adaptive, ethical, and accountable. The activity was carried out at STAI Putra Galuh Ciamis on February 2, 2026, by involving 120 students through participatory training in the form of material presentations, questions and answers, case discussions, decision-making simulations, reflections, and evaluations before and after the activity. The evaluation includes understanding digital leadership, organisational governance readiness, and digital communication and collaboration. Based on the draft dataset, the average overall score increased from 2.83 to 4.34 or by 53.04%. The highest increase was in organisational governance at 57.14%, followed by digital leadership at 51.84% and digital communication and collaboration at 50.57%. Participant satisfaction reached an average of 4.38 on a scale of 5. These results show the potential of training in improving participants' understanding and readiness, especially in planning, task sharing, communication, documentation, and organisational evaluation. Further assistance is needed to support the sustainability of the implementation of competencies in student organisation activities.